THE ANALYSIS STUDY OF ONE-STEP COMPARED WITH TWO-STEP GESTATIONAL DIABETES SCREENING AND PREGNANCY OUTCOMES: A COMPREHENSIVE SYSTEMATIC REVIEW - Wijaya, Vennylia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Gestational diabetes mellitus (GDM) is a condition of glucose intolerance developed during pregnancy. Many women with GDM experience pregnancy -related complications, which primarily affect the fetus and include macrosomia, congenital malformations, prematurity, neonatal intensive care unit (NICU) admission, and respiratory distress syndrome. The aim: The aim of this study to show about the analysis study of one-step compared with two step gestational diabetes screening and pregnancy outcomes. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Patients undergoing one- and two-step testing had equal rates of LGA infants, despite a greater likelihood of GDM diagnosis and treatment with one-step testing. Our findings favor two-step testing to minimize the increased burden of GDM diagnosis resulting from one-step testing. However, understanding the long-term implications of such a strategy across the life course is critically important to inform the public health path forward.